Mitt liv som hund = My life as a dog [videorecording (DVD)] - Hallström, Lasse; Glanzélius, Anton, 1975-; Brömssen, Tomas von, 1943-; Lidén, Anki; Jönsson, Reidar, 1944- (Criterion collection, 2003)
Ingemar is a working-class 12-year old boy who is sent to live with his uncle after his mother falls ill. There, he takes refuge from his troubles with the help of the town's warmhearted eccentrics. A bittersweet evocation of the struggles and joys of childhood and the pains of coming-of-age.